Ethnographic filmmaking as narrative capital enhancement among Atauro diverwomen: a theoretical exploration. Issue 3 (2nd April 2016) - Alonso-Población, Enrique; Fidalgo-Castro, Alberto; Palazón-Monforte, David
ABSTRACT: This article reports on a project involving the development and release of an ethnographic film about the women divers of Atauro Island, Timor-Leste, and suggests a theoretical framework to interpret its outcomes. It describes the project aims and the filmmaking process, and reports on its results. In doing so, the paper explores the potential use of an agent-based concept of narrative capital focused on collective agents. The article suggests that the ideas of narrative capital and transformations of capital by collective agents can provide a valuable interpretative framework for the design, implementation, and analyses of results of development interventions involving filmmaking.